Gorlin-Goltz Syndrome: case report and review of literature - Rahde Bischoff, Adrianne; Mercedes Timana Delgado, Yina; de Oliveira Poswar, Fabiano; Tarasconi Ruschel, Eduardo; Kohls Toralles, Eduardo; Lona Curubeto Lona de Miranda, Gabriel; Francisco Silveira Rita, Mario (Clinical and Biomedical Research, 2014)
Description of a case report of Gorlin-Goltz Syndrome diagnosed in a male newborn who presented increased head circumference and bifid ribs. Mother and grandmother presented typical physical findings of the syndrome, including palmar pits, odontogenic cysts, and history of multiple skin cancer resections. The diagnosis was based on clinical findings of three relatives. A literature review is also presented.